PENGEMBANGAN MULTIMEDIA INTERAKTIF PADA MATA PELAJARAN SKI UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA DI PERGURUAN THAWALIB PUTRI PADANG PANJANG - Depki Elnanda (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
This research started from a preliminary study that Perguruan Thawalib Putri Padang Panjang on SKI grade VIII revealed that the learning process were not interactive multimedia. This study was purposed at developing an Interactive Multimedia by using software macromedia director mx. This paper related to the recent research in England, Kenya, New York, Korea, Mangalore, Indiana, Taiwan, Turky and Malaysia that interactive multimedia was interesting and effective to assist teachers on delivering learning materials. This study used research and development by applying 4-D models (define, design, develop and disseminate). The data were obtained from SKI teachers and students grade VIII which consist of 34 students. The observation, interview, questionnaire, documentation and testing were used as instruments. The findings revealed that interactive multimedia by using macromedia director mx to Islamic History was successful and considered valid, practical, and effective and it increased students’ learning motivation. Keywords: Interactive Multimedia, Software Macromedia Director Mx, Islamic History, Students’ Learning Motivation, Perguruan Thawalib Putri Padang Panjang